Dry needling in cervical pain therapy: literature Reviews - Bojan Pavlović; Ana Pavlović (Биомедицинска истраживања, 2024)
Neck pain, considering its prevalence and rate of disability, represents a significant public health problem, and we believe that the promotion of new effective methods is necessary in its treatment. Among the many therapeutic possibilities described so far, one such is dry needling (DN). This literature Reviews aims to analyze how effective dry needling has proven to be in the treatment of neck pain. Existing works indicate the possibility of a good response from patients when using dry needling in the treatment of neck pain, so we believe that this possibility should be given more attention in practice and research.
Keywords: dry needling; cervicalgia; pain; treatment